Posterior reversible encephalopathy syndrome in an oncological normotensive patient: evidence for a pathogenic role of concomitant low magnesium serum levels and chemotherapy treatment - Zappia, Federica; Verzicco, Ignazio; Simoni, Riccardo; Ferrari, Massimiliano; Coghi, Pietro; Bozzetti, Francesca; Cannone, Valentina; Volpi, Riccardo; Cabassi, Aderville (Acta Biomedica Atenei Parmensis, 2020)
Background: Posterior reversible encephalopathy (PRES) is a rare syndrome characterized by headache, confusion, seizures, visual changes and white matter edema at radiological imaging. Its pathophysiology is not clarified and different causes, including uncontrolled hypertension, eclampsia, chemotherapy and hypomagnesemia have been suggested. Case report: A woman affected by stage IV breast cancer with lower extremity deep vein thrombosis treated with low-molecular-weight-heparin, currently in therapy with Palbociclib/Fulvestrant (antiCDK4 and 6/estrogen receptor antagonist) but previously treated with several other chemotherapy lines (including VEGF inhibitor bevacizumab), was admitted to our Internal Medicine department because of ascites and abdominal pain. She was treated with diuretics (and paracentesis). Recently (six-month earlier) a pan-encephalic radiotherapy was done because of brain and skull metastasis. Among blood tests, low serum levels of hypomagnesemia were observed. She developed PRES that rapidly progressed to lethargy, unresponsiveness till coma without changes in blood pressure. Magnetic Resonance Imaging study showed bilateral parieto-occipital edema and a thrombosis of left transverse and sigmoid sinuses. Anti-edema therapy, intravenous supplementation of magnesium and decoagulation were started, with complete and rapid recovery (within 18 hours) of clinical and radiologic changes. Conclusions: PRES diagnosis was based on the rapid clinical recovery after antiedema treatment and magnesium supplementation. Low magnesium level related to both diuretic and Fulvestrant/Palbociclib therapies and recent radiotherapy can represent potential mechanisms favouring PRES development. The previous bevacizumab treatment may also be involved as a PRES predisposing factor. The concomitant occurrence of cerebral thrombosis can have precipitated the clinical situation.